The Effectiveness of Cooperative Learning in Enhancing EFL Writing Skills: The Case of 3rd Year EFL Students in Djeridane Lazhari Secondary School – Sidi Makhlouf – Laghouat - Haimoud , Houda; Gasmi, Mustapha (Faculty of Letters and Foreign Languages Department of English, 2025)
The present research attempts to investigate the effectiveness of cooperative learning in enhancing EFL writing skills of third year secondary school students. The study aims to determine whether CL activities improve EFL students‟ writing performance in terms of grammar, vocabulary, organization, and coherence, and whether engaging in CL has a positive effect on students‟ attitudes. The study also aims to highlight the main challenges in implementing CL. In order to reach the aim of this study, descriptive analytical method and quantitative approach were adopted. Besides, two questionnaires have been submitted to a sample composed of 42 third year students in Sidi Makhlouf secondary school (Djeridane Lazhari) and ten (10) teachers from two towns, Sidi Makhlouf and Laghouat. The results of the questionnaires confirmed the hypothesis that CL helps students improve their grammar, gain new vocabulary, and structure their writing with clear organization and smooth coherence. Moreover, CL increases students‟ confidence, motivation, and engagement in their writing. Additionally, the results also revealed that teachers may find difficulties in implementing CL such as time management, organization of groups, and students‟ assessment. Accordingly, it is recommended to implement cooperative learning in improving EFL students‟ writing skills.